Encyclopedia: Non-Liquet - Atip Latipulhayat (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Non-Liquet means, literally, "it is not clear" in Latin. This refers to the situation when courts are not able to render a decision on a case, because of the existence of a gap in the law, or because of the inadequacy of the legal basis for deciding the case. However, the failure of the court to make a decision does not necessarily mean it constitutes a non-liquet. This may occurred due to the absence of jurisdiction of the court over the case, or the parties do not have legal standing. In short, it can be said that non-liquet happened because the court failed to make a decision due to the absence of applicable rule of law. At the practical level, it raises the question on whether non-liquet occurred because of inability of judges or arbitrators to make a decision on a specific case or inadequacy of the underlying legal systems itself. In the first sense, it refers to what scholars say as ‘decision-making non-liquet’, and ‘systemic non-liquet’ for the second sense. DOI: https://doi.org/10.22304/pjih.v5n3.a0